Evidence of Construct Validity of Computer-Based Tests for Clinical Reasoning: Instrument Validation Study - Tianming Zuo; Baozhi Sun; Xu Guan; Bin Zheng; Bo Qu (JMIR Publications, 2021)
BackgroundClinical reasoning (CR) is a fundamental skill for all medical students. In our medical education system, however, there are shortcomings in the conventional methods of teaching CR. New technology is needed to enhance our CR teaching, especially as we are facing an influx of new health trainees. China Medical University (CMU), in response to this need, has developed a computer-based CR training system (CMU-CBCRT). ObjectiveWe aimed to find evidence of construct validity of the CMU-CBCRT. MethodsWe recruited 385 students from fifth year undergraduates to postgraduate year (PGY) 3 to complete the test on CMU-CBCRT. The known-groups technique was used to evaluate the construct validity of the CBCRT by comparing the test scores among 4 training levels (fifth year MD, PGY-1, PGY-2, and PGY-3). ResultsWe found that test scores increased with years of training. Significant differences were found in the test scores on information collection, diagnosis, and treatment and total scores among different training years of participants. However, significant results were not found for treatment errors. ConclusionsWe provided evidence of construct validity of the CMU-CBCRT, which could determine the CR skills of medical students at varying early stage in their careers.